2018
DOI: 10.1186/s12896-018-0467-5
|View full text |Cite
|
Sign up to set email alerts
|

Development of a vitrification method for preserving human myoblast cell sheets for myocardial regeneration therapy

Abstract: BackgroundTissue-engineered cardiac constructs have potential in the functional recovery of heart failure; however, the preservation of these constructs is crucial for the development and widespread application of this treatment. We hypothesized that tissue-engineered skeletal myoblast (SMB) constructs may be preserved by vitrification to conserve biological function and structure.ResultsScaffold-free cardiac cell-sheet constructs were prepared from SMBs and immersed in a vitrification solution containing ethy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 39 publications
(39 reference statements)
0
18
0
Order By: Relevance
“…To date, CBRT has been the mainstream approach, and numerous studies have reported its usefulness with different types of stem cells [30,31], including MSCs [8,9]. CBRT requires an in-house cell-processing center with an aseptic environment in the hospital [34]. Because drug-induced regenerative therapy does not require any cell culture, the quality of those cells is more easily maintained than with CBRT.…”
Section: Plos Onementioning
confidence: 99%
“…To date, CBRT has been the mainstream approach, and numerous studies have reported its usefulness with different types of stem cells [30,31], including MSCs [8,9]. CBRT requires an in-house cell-processing center with an aseptic environment in the hospital [34]. Because drug-induced regenerative therapy does not require any cell culture, the quality of those cells is more easily maintained than with CBRT.…”
Section: Plos Onementioning
confidence: 99%
“…More studies have tried to preserve cell sheet by cryopreservation and have successfully cryopreserved limbal stem cell sheets [ 14 ], chondrocyte sheets [ 15 ], myoblast cell sheets [ 16 ], and mesenchymal stem cell sheets [ 17 ], in which 48–97% cell viability was reported. However, cryopreservation of ECSs remains a challenge because the ability to tolerate cryopreservation varies by cell type.…”
Section: Discussionmentioning
confidence: 99%
“…Cell sheet technology has been developing for the past decade to target the delivery of cell sheets onto damaged organs. Success of both cell sheet engineering and transplantation have been reported in numerous articles; however, only three recent publications have reported the vitrification of cell sheets (Maehara et al, ; Ohkawara et al, ; Tani et al, ). Little is known about cell sheet vitrification; more studies are needed to increase our knowledge and to improve the vitrification methodology of cell sheets.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, we focused on analyzing CAOMECS stored in the absence of vitrification solutions. In addition, Ohkawara et al showed that human myoblasts cell sheets vitrified from 2 days to 3 months had the same curative effect on the heart after transplantation, indicating that the time of storage has no effect on the curative properties of the cell sheets (Ohkawara et al, ). These authors also mentioned that the cryopreserved cell sheets by slow freezing were not capable of rebuilding the extra cellular matrix upon thawing, confirming the need for a fast freezing of cell sheets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation